(untitled) (Research, Society and Development, 2022)
The presente study aimed to know the social representations about violence against children for women who practiced it. This is a qualitative and exploratory study, which included five women who practiced violence against children and who were undergoing psychotherapeutic treatment at an institution providing assistance to families in situations of violence in a municipality in southern Brazil. Data were collected in the period between July and August 2013, through semi-structured interviews and construction of a Genogram. Data analysis took place through Discursive Textual Analysis anchored in the Theory of Social Representations. The results showed that women aggressors build their representations in the conception of the superiority of the adults in relation to the child, with this conception anchored in the social imaginary historically constructed and shared collectively. The participants’ social representations are related to the historical aspects linked to the meanings attributed to the child and childhood added to their experiences. In this sense, it is necessary to help parents recognize their children as subjects of rights and to find strategies for self-control and handling situations of conflict with their children.